Multi-Track Economic Diplomacy Indonesia Facing EUDR (European Union Deforestation Regulation) Trade Barriers - Risalatu Mirajiah (Journal of Social Research, 2026)
Crude Palm Oil (CPO) is one of the strategic export commodities for the Indonesian economy. However, the export of this commodity faces significant challenges following the implementation of the European Union Deforestation Regulation (EUDR), which mandates strict deforestation-free due diligence. This regulation has the potential to act as a discriminatory non-tariff barrier, threatening Indonesian palm oil's market access in Europe. This study aims to analyze the economic diplomacy strategies implemented by the Indonesian Government in responding to the EUDR policy. The research method used is descriptive qualitative with a library research approach, utilizing secondary data sources such as official government documents, international institutional reports, and academic literature. The findings reveal that Indonesia’s response is structured through a multi-track economic diplomacy approach encompassing three main pillars: bilateral engagement with European Union member states to negotiate technical flexibility and mitigate risk classification; multilateral strategies through dispute mechanisms at the World Trade Organization (WTO) and coalition-building via the Council of Palm Oil Producing Countries (CPOPC); and domestic-commercial measures through the strengthening of Indonesian Sustainable Palm Oil (ISPO) certification as a source of bargaining power. These findings demonstrate that Indonesia’s diplomacy is not merely reactive but represents an integrated effort to enhance its negotiating position in the face of regulatory pressure, although its effectiveness remains constrained by domestic implementation challenges, particularly in smallholder compliance and governance capacity. The success of Indonesia’s economic diplomacy in responding to EUDR ultimately depends on the alignment between international negotiation strategies and the strengthening of domestic institutional capacity.